Exploring Green Energy Adoption: A Comprehensive Study on India’s Sustainable Future Trends using Stimulus-Organism- Response Model - Chawla, Udit; Kraiwanit, Tanpat; Mohnot, Rajesh; Dugad, Reyaansh (International Review of Management and Marketing, 2025)
This artifact examines the inhibitors and organizers of green energy technology in India, with an emphasis on consumers’ viewpoints on the transfer to renewable energy. The study aims to regulate the impression and connection of perceived trust, attitude, perceived usefulness, perceived environmental concern, and behavioural intention on consumers’ purchases of green energy. The study settles that poise in green energy suppliers, a favourable attitude toward environmental conservation, and apparent advantages such as prices and consequences are significant drivers of green energy. Moreover, the study emphasizes the prominence of demonstrative appeals and environmental signs in shaping sustainable consumption habits. These findings also provide useful recommendations for directors focused on green energy, such as building trust, accentuating the reimbursements of using clean technologies, and confirming the compatibility of marketing posts with consumer values, all of which are critical for the region’s broader approval of renewable energy.